Case Report : Penerapan Prone Positioning dan Nesting dalam Menstabilkan Status Hemodinamik pada Bayi RDS - Dinda Asmara Varnelia; Cantika Azahra; Erna Julianti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract Respiratory Distress Syndrome (RDS) is a major cause of morbidity and mortality in neonates, especially premature infants, due to impaired gas exchange and ineffective breathing patterns. Evidence-based management is needed to maintain physiological stability. This study aims to apply prone positioning and nesting in stabilizing the fisiology of infants with RDS. This is a descriptive study with a case study approach consisting of assessment, diagnosis, intervention, implementation, and evaluation. The sample in this study amounted to 2 infants with inclusion criteria of 32 weeks gestation, weight less than 2,500 grams and using CPAP with PEEP 6 FiO2 21%. The intervention was given in the form of a prone position fixed with nesting for 3 hours, twice a day, for three days. Parameters of respiratory frequency (RR), heart rate (HR), and oxygen saturation (SpO?) were monitored before, during, and after the intervention. The results showed a mean decrease in HR of 1.8–6%, a decrease in RR of up to 12.5%, and an increase in SpO? of 1–2%, with all parameters within the normal neonatal range. This combination of interventions has been shown to help optimize oxygenation, reduce respiratory workload, and maintain fisiology, stability. In conclusion, the application of prone positioning and nesting showed improvements in infant physiological parameters, so this non-pharmacological intervention can support the respiratory function of infants with RDS and is worthy of recommendation for care practices in the NICU. Keywords: Ineffective breathing pattern, nesting, preterm infants, prone positioning, Respiratory Distress Syndrome, CPAP